Analysis and recommendations for the continuity of the initiative Your Competences in Science of the CONICYT “explora" program, in educational establishments of Chile - Arismendi, Paula (Journal Studies of Public Policy, 2016)
This paper describes the design of the initiative “Tus Competencias en Ciencias” using a qualitative exploratory-descriptive methodology, which analyzes the results of implementation of TCC in its eight years of operation. Surveys were administered to TTC teachers and Directors of Proyectos Asociativos Regionales, to know their perception about the implementation of workshops and success factors that could assist in the continuation or massivity of TCC. We concluded that there is a positive perception of the initiative, but requieres adjustments to its continuity. The Explora program of CONICYT is visualized as an entity that does not have the organizational capacity to assume the expansion of the initiative, however, it could be solved if it has the financial support of the Ministry of Education.